Sustainable Zeolite–Silver Nanocomposites via Green Methods for Water Contaminant Mitigation and Modeling Approaches - Reyes-López, Simón Yobanny (2024)
This study explores cutting-edge and sustainable green methodologies and technologies for the synthesis of functional nanomaterials, with a specific focus on the removal of water contaminants and the application of kinetic adsorption models. Our research adopts a conscientious approach to environmental stewardship by synergistically employing eco-friendly silver nanoparticles, synthesized using Justicia spicigera extract as a biogenic reducing agent, in conjunction with Mexican zeolite to enhance contaminant remediation, particularly targeting Cu2+ ions. Structural analysis, utilizing X-ray diffraction (XRD) and high-resolution scanning and transmission electron microscopy (TEM and SEM), yields crucial insights into nanocomposite structure and morphology. Rigorous linear and non-linear kinetic models, encompassing pseudo-first order, pseudo-second order, Freundlich, and Langmuir, are employed to elucidate the kinetics and equilibrium behaviors of adsorption. The results underscore the remarkable efficiency of the Zeolite–Ag composite in Cu2+ ion removal, surpassing traditional materials and achieving an impressive adsorption rate of 98% for Cu. Furthermore, the Zeolite–Ag composite exhibits maximum adsorption times of 480 min. In the computational analysis, an initial mechanism for Cu2+ adsorption on zeolites is identified. The process involves rapid adsorption onto the surface of the Zeolite–Ag NP composite, followed by a gradual diffusion of ions into the cavities within the zeolite structure. Upon reaching equilibrium, a substantial reduction in copper ion concentration in the solution signifies successful removal. This research represents a noteworthy stride in sustainable contaminant removal, aligning with eco-friendly practices and supporting the potential integration of this technology into environmental applications. Consequently, it presents a promising solution for eco-conscious contaminant remediation, emphasizing the utilization of green methodologies and sustainable technologies in the development of functional nanomaterials.